The Conservative Challenge to Caring for Compensated Caregivers - Peggie R. Smith (Washington University Journal of Law & Policy, 2020)
As more households seek home care workers to provide care for elderly and disabled family members, conservative attacks on workers’ unionization efforts threaten to destabilize the industry. This article discusses the supply and demand concerns within the industry, and considers the conservative attack on home care workers. It concludes by exploring the proposed federal domestic workers bill of rights and recommends proactive measures for states to help fortify the industry.
Keywords: conservative; home care; caregivers; caregiver; union; unionization